Supervisory Function of Prosecution Service as an Object of Historic and Legal Analysis - SUGAIPOVA, Elina Akhmedovna; HASIEVICH, Movlad Geldibaev (Journal of Advanced Research in Law and Economics, 2017)
The research analyses the emerging supervisory institutes and touches historic prerequisites for the development of supervisory function of the Russian prosecution service.